Identification of a novel large CASR deletion in a patient with familial hypocalciuric hypercalcemia - García-Castaño, Alejandro (Endocrinol Diabetes Metab Case Rep, 2018)
Familial hypocalciuric hypercalcemia type I is an autosomal dominant disorder caused by heterozygous loss-of-function mutations in the CASR gene and is characterized by moderately elevated serum calcium concentrations, low urinary calcium excretion and inappropriately normal or mildly elevated parathyroid hormone (PTH) concentrations. We performed a clinical and genetic characterization of one patient suspected of familial hypocalciuric hypercalcemia type I. Patient presented persistent hypercalcemia with normal PTH and 25-hydroxyvitamin D levels. The CASR was screened for mutations by PCR followed by direct Sanger sequencing and, in order to detect large deletions or duplications, multiplex ligation-dependent probe amplification (MLPA) was used. One large deletion of 973 nucleotides in heterozygous state (c.1733-255_2450del) was detected. This is the first large deletion detected by the MLPA technique in the CASR gene. LEARNING POINTS: Molecular studies are important to confirm the differential diagnosis of FHH from primary hyperparathyroidism. Large deletions or duplications in the CASR gene can be detected by the MLPA technique. Understanding the functional impact of the mutations is critical for leading pharmacological research and could facilitate the therapy of patients.